One-pot synthesis and photocatalytic activity of SnO2/TiO2 nanocomposite thin film. (May 2014) - Liu, H. F.; Zheng, B. J.; Dao, A. Q.; Yi, S. T.; Jiang, D. S.; Fu, C. Y.; Xiao, F.
Abstract : SnO2 /TiO2 nanocomposite thin films on glass plate and nickel screen were prepared by liquid phase deposition method. The degradation experiments of methylene blue (MB) indicated that the composite film exhibited higher photocatalytic activity than pure TiO2 film. The improvement of the composite film photocatalytic activity can be attributed to the infiltration into TiO2 lattice of nano-SnO2 . The optimal ratio of doped SnO2 was 8%, with a 98·79% degradation rate in 5 h. The photocatalytic performance of SnO2 /TiO2 film on nickel screen was obviously superior to that of nonconductive glass slide. The degradation of chemical oxygen demand (COD) was evaluated to investigate the mineralisation of MB. The COD removal rate increased with longer irradiation time and lagged behind the MB degradation rate.